Benzothiadiazole-based D-π-A-π-D fluorophores: Synthesis, self-assembly, thermal and photophysical characterization. (December 2017) - Fang, Haipeng; Gao, Hongfei; Wang, Tingyan; Zhang, Bei; Xing, Wei; Cheng, Xiaohong
Abstract: A symmetrical linear D-π-A-π-D hexacatenar compound with 2, 1, 3-benzothiadiazole as the acceptor core connected at its 4, 7 position with phenylthienylethynyl spacers has been designed and synthesized. This compound displays liquid crystalline property with oblique columnar mesophase and forms an organogel in dichloromethane. The investigation of photophysical and electrochemical properties reveals that this compound can exhibit broad and strong absorption band at the range of 300–700 nm with a low energy gap in solid state, meanwhile it exhibits highly red fluorescent emission and large Stokes shifts. Graphical abstract: Highlights: BTD-based D-π-A-π-D fluorophoreI has been synthesized in high yield. I self-assembles into an oblique columnar mesophase and organogel with a fibrous aggregate. I exhibits broad absorption band and red fluorescent emission with large Stokes shifts.